From the Alter Ego to the Alter Identicus: The Transformation of the Epistemological Approach to the other and its Implications in Child Psychiatry (London Journal of Research In Humanities and Social Sciences, 2025)
The alter identicus has dismissed the alter ego in late modernity, with repercussions  for the way psychiatrists view the other. After examining the notions of limit and  situation for each of these two ways of viewing the other, we will examine their  consequences for diagnostic development. We will detail the example of the ADI-R  and the ADOS in the diagnosis of autism spectrum disorders (ASD). We will question  the usefulness of defining very broad markers of belonging (alter identicus) that seem  to miss their target : to understand a neuroconstructivist development process in  which the patient’s creativity (alter ego) contributes significantly to the development  of a divergent trajectory.
Keywords: Human Rights; Cultural relativism; Human rights watch; Inherited; Male guardianship; Al Shafallah.; justice.; Justice Administration; Courts of First Instance; Court Organisation; Judicial Institution; Integration; Pedagogy; Generative Artificial Intelligence (GenAI); posthumanist; Generation Z; Quality of Employment IMCE; Intergenerational Precariousness; Decent Work.; alter ego; alter identicus; diagnosis by discrimination; diagnosis by accumulation; ADI-R; ADOS; neuroconstructivist developmental hypothesis.